Kajian Penggunaan Limbah Plastik Sebagai Campuran Agregat Beton - Suwarno, Anung; Sudarmono, Sudarmono (Politeknik Negeri Semarang, 2015)
This paper presents the study of the use of waste plastic bags as a mixture of fine aggregate in concrete production 1 pc: 2 Psr: 3 Split, variations in the mix of plastic is added the mortar 0, 1, 1.5, 2, 2.5, 3, 4, and 5 %. Any variation tested mixture compressive strength and tensile strength. With this method can further determined that the most optimum addition of plastic to be used as concrete mix. From the test results showed that the addition of plastics 5% increases the tensile strength of concrete approximately 50% compared with no addition of plastic, in contrast with the addition of the same plastic reduces the compressive strength of 47 %. From these results it can be stated that the addition of plastics will increase its tensile strength so that the inner structure of the fiber tensile cracks will not occur, with the addition of waste plastic bags reduces the density of concrete, so the construction is lighter.